The effect of welding time on the tensile load capacity of dissimilar-metal stainless steel-carbon steel TIG-Spot welded joint - Nugroho, Aris Widyo; Prayitno, Hadi; Rahman, Muhammad Budi Nur (Universitas Muhammadiyah Yogyakarta, 2024)
This study examines the influence of welding time on the tensile load capacity of spot TIG welds using stainless steel and low carbon steel plates (100 mm × 30 mm × 0.8 mm) as per AWS D8.9 standards. A constant welding current of 90 A was applied, with 2-, 3-, 4-, and 5-seconds welding times. Tensile properties, microstructure, and hardness were analyzed using a universal tensile machine, an optical microscope, a scanning electron microscope, and a Vickers hardness tester. Results show that the tensile load capacity increases with welding time, peaking at 4 seconds (≈4300 N), before dropping significantly at 5 seconds (≈4000 N) due to overheating, which weakens the joint. The findings highlight the critical role of optimizing welding time to maximize joint strength while preserving the material's microstructure. Overextended welding times compromise performance, emphasizing the balance required for achieving durable welds.